Attachment Style and Partnership Success: The Mediating Role of Forgiveness - Ranđelović, Kristina M.; Goljović, Nikola; Mladenović, Nataša (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
A successful partnership implies one’s ability to attract and retain a partner. Readiness to forgive contributes to the renewal and improvement of broken relationships, while an attachment style plays an important role in the formation of internal ‘working models’ that serve as ‘guidelines’ for the formation of new relationships. The goal of this study was to investigate whether there is a connection between attachment and success in maintaining a partnership, and if so, whether that relationship is direct or mediated by the capacity to forgive. Based on the results obtained with the Mediation Analysis with Multiple Mediators, we found that insufficient effort in the process of finding a partner is not directly associated with Avoidance, i.e., the negative working model of others; this connection is created indirectly through the strategy to avoid forgiveness. The sample used in this study is representative and included 387 participants, 82,7% of which were female participants between 18 and 40 years of age (AS = 23,90; SD = 4,22). The instruments used were the Mating Effort Scale (Apostolou et al., 2018), Partner Selectivity Scale (Apostolou et al., 2018), the Scale for Success in Finding a Partner (Apostolou et al., 2018), the Tendency to Forgive Scale (McCullough, Root, & Cohen, 2006), Affective Partner Attachment Scale (Brennan, Clark & Shaver, 1995). The results obtained indicate that insufficient effort in the process of finding a partner is not directly associated with Avoidance; this connection is created indirectly through the strategy to avoid forgiveness (ab=-,043, [-,077, -,017]). As for the connection between Effort and Anxiety, it is mediated by the Revenge dimension (ab = -,051, [-,080, -,026]). Forgiveness avoidance has been shown to be a statistically significant mediator in the relationship between Failure to Find a Partner and Avoidance (ab = -,029, [-,052, -,010]). All obtained mediations are partial. This research shows that success in maintaining a relationship, selectivity when looking for a partner and the effort invested to start and maintain a relationship are closely associated with a person’s emotional development: his/her vision of him/herself, vision of others and emotional capacity developed through life, such as the tendency to forgive. The findings of this research would be much more valuable if the research was conducted on both partners in a certain relationship and if the situation related to forgiveness was kept under control, which is a recommendation for other studies.
Keywords: Attachment; partnership success; forgiveness; forgiveness strategies